96=8(6-a)

Simple and best practice solution for 96=8(6-a) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 96=8(6-a) equation:


Simplifying
96 = 8(6 + -1a)
96 = (6 * 8 + -1a * 8)
96 = (48 + -8a)

Solving
96 = 48 + -8a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '8a' to each side of the equation.
96 + 8a = 48 + -8a + 8a

Combine like terms: -8a + 8a = 0
96 + 8a = 48 + 0
96 + 8a = 48

Add '-96' to each side of the equation.
96 + -96 + 8a = 48 + -96

Combine like terms: 96 + -96 = 0
0 + 8a = 48 + -96
8a = 48 + -96

Combine like terms: 48 + -96 = -48
8a = -48

Divide each side by '8'.
a = -6

Simplifying
a = -6

See similar equations:

| u=4.20-0.75s | | 6m-8=4-3m | | 12x-4(x+4)=3+5(4x+1) | | 12x-4(x-4)=3+5(4x+1) | | 47a+56=-320 | | 12+5m=-3 | | x-(8x+5)=15+2(11-7x) | | 3+2x=3(2x+4)-5(x-2) | | 3x-(8-x)=5(3-x)+4 | | -7+2x=-25-x | | x-(8-x)=5(3-x)+4 | | 10+12=-34+x | | 2x+10-7x=3(x-5)+1 | | 3*(x+2)=3x+32 | | 7(2x+1)=5x+16 | | 9x+8+2x+6=7x+2 | | 8x-5x=8 | | 10p-4=86 | | -7+8x-19=15+3(x-17) | | 5/m=8/6 | | 2[t+6]-1=9 | | 3/n=10/7 | | x+8(12-x)=7x-(5x-42) | | 6/a=5/7 | | -16=-4[v+3] | | 1/2-3x=-1/2 | | -4+5x=36 | | x+8(12-x)=7x(5x-42) | | -8x-5x-96=60 | | 8/3=n/4 | | x-7x-61=23 | | 7=2[r+6]-5 |

Equations solver categories